PERANAN BUMDES GUHA BAU DALAM MEMANFAATKAN DANA DESA UNTUK PENGEMBANGAN DESA WISATA KERTAYASA KECAMATAN CIJULANG KABUPATEN PANGANDARAN - Diniasari, Gina Mutia; Dahtiah, Neneng (KRISNA: Kumpulan Riset Akuntansi, 2023)
Kertayasa Tourism Village is the winner of the National Tourism Village Competition organized by the Kemendes PDTT. After becoming a champion in national-level competition, Kertayasa Tourism Village has become the attention of many parties regarding how Kertayasa Tourism Village can achieve its achievements. The management of tourism in the Kertayasa Tourism Village is handed over to the Guha Bau Village-Owned Enterprises (BUMDes). During the process, Guha Bau Village-Owned Enterprises received capital from the Village Fund through equity participation for Village-Owned Enterprises. This study aims to find out how Guha Bau Village-Owned Enterprises utilize village funds provided by Kertayasa Village through equity participation for Village-Owned Enterprises in the development of Kertayasa Tourism Village and what factors support and hinder Guha Bau Village-Owned Enterprises in developing Kertayasa Tourism Village. This research is descriptive qualitative research with data collection techniques conducted through interviews, observation, and documentation. The validation technique used is triangulation, using reference materials and member checks. Qualitative data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that Guha Bau Village-Owned Enterprises acts as a business actor or manager of all tourism objects in the Kertayasa Village area. It can be concluded that Guha Bau Village-Owned Enterprises can utilize village funds well through 3 stages, namely planning, implementation, and accountability. There are supporting and inhibiting factors in the process of developing the Kertayasa Tourism Village by Guha Bau Village-Owned Enterprises.